PENTINGNYA PENDIDIKAN AGAMA KATOLIK BAGI SISWA-SISWI KATOLIK MENURUT CATECHESI TRADENDAE - Muaja, David Christopher Andrew; Sunlety, Firmus; Ruban, Teresia Lian (Pineleng Theological Review, 2024)
This paper aims to explain the importance of catechesis for Catholic students in schools. In this regard, the authors would like to analyze some relevant points of Catechesi Tradendae regarding catholic education. Generally speaking, the document talks about the importance of catechism in the present world. One of the basic ideas is to emphasize that catechesis is an important task for every Catholic for the development of their faith. This document also presents Pope John Paul II's efforts to support the development of the Church through catechesis. Finally, this document states that the formation of people of God cannot be separated from catechesis. A good spiritual formation will bring about a good development of the catholic faith.